2011
DOI: 10.1007/s00894-011-1189-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling of cytochrome b 5 with a single cytochrome c-like thioether linkage

Abstract: Bovine liver cytochrome b (5) (cyt b (5)), with heme bound noncovalently, has been converted into a cyt c-like protein (cyt b (5) N57C) by constructing a thioether linkage between the heme and the engineered cysteine residue. With no X-ray or NMR structure available, we herein performed a molecular modeling study of cyt b (5) N57C. On the other hand, using amino acid sequence information for a newly discovered member of the cyt b (5) family, domestic silkworm cyt b (5) (DS cyt b (5)), we predicted the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Due to the spatial position, Cys57 forms a typical thioether linkage with a heme 4‐vinyl group, whereas Cys71 forms an unusual [heme‐CO‐CH 2 ‐S‐CH 2 ‐C α ] linkage with a heme 2‐vinyl group (Figure ). Molecular modeling indicated that covalent heme attachment to the polypeptide chain does not alter the overall structure of Cyt b 5 . The c ‐type Cyt b 5 , which differs from wild‐type (WT) Cyt b 5 by only two covalent linkages, provides an ideal protein model to investigate the structure and function of heme proteins in non‐native states and also the consequences of the heme‐to‐protein attachment.…”
Section: Figurementioning
confidence: 82%
See 1 more Smart Citation
“…Due to the spatial position, Cys57 forms a typical thioether linkage with a heme 4‐vinyl group, whereas Cys71 forms an unusual [heme‐CO‐CH 2 ‐S‐CH 2 ‐C α ] linkage with a heme 2‐vinyl group (Figure ). Molecular modeling indicated that covalent heme attachment to the polypeptide chain does not alter the overall structure of Cyt b 5 . The c ‐type Cyt b 5 , which differs from wild‐type (WT) Cyt b 5 by only two covalent linkages, provides an ideal protein model to investigate the structure and function of heme proteins in non‐native states and also the consequences of the heme‐to‐protein attachment.…”
Section: Figurementioning
confidence: 82%
“…Molecular modeling indicatedt hat covalent heme attachment to the polypeptide chain does not alter the overall structure of Cyt b 5 . [12] The c-type Cyt b 5 ,w hich differs from wild-type (WT) Cyt b 5 by only two covalent linkages, provides an ideal protein model to investigate the structure andf unction of heme proteins in non-native states and also the consequences of the heme-to-protein attachment. The double-mutant N57C/S71C Cyt b 5 was expressed and purified as previously described.…”
mentioning
confidence: 99%
“…Molecular modeling showed that a single thioether bond in N57C cyt b 5 does not alter the overall protein structure (Fig. 2D, [26]). The double thioether bonds in R98C/Y101C cyt b 562 , termed cyt cb 562 , were confirmed by an X-ray crystal structure (Fig.…”
Section: Thioether Bondmentioning
confidence: 95%
“…With an emerging understanding, albeit not complete, of the diverse cross-links in natural heme proteins, most of these cross-links have been successfully recreated in natural or de novo proteins, such as Cys-heme [24,26,27,33,[41][42][43][44][45], Met-heme [53], His-heme [70][71][72], Trp/Tyr-heme [78] and Glu/Asp-heme [82,106,[108][109][110][111] cross-links. These achievements, in turn, have enhanced our knowledge of how heme-protein cross-link regulates the structure and function of heme proteins in nature.…”
Section: Summary and Perspectivementioning
confidence: 99%
See 1 more Smart Citation